Digital Rights: Feminist Activism of Southeast Asia Freedom of Expression Network (SAFEnet) in Online Gender-Based Violence (GBV) Advocacy - Asriasni, Rini (The Easta Journal Law and Human Rights, 2025)
Globalization has brought significant changes in global social life, one of which is the presence of digital technology and online platforms. Technology facilitates transnational relations that are vulnerable to digital rights violations. This research discusses the role of SAFEnet or Southeast Asia Freedom of Expression Network in advocating online gender-based violence (GBV). This research uses the concept of digital activism by Vogt and Chen as an approach to analyze the advocacy of GBV cases by SAFEnet. This research found that SAFEnet conducts digital activism such as organizing collective identities, coordinating networks, producing knowledge, disseminating information, and mobilizing actors.